Аналитический электрофорез в свободном потоке клеток и белков - Габуев, И.С.; Мазанов, А.Л.; Брезгунов, В.Н.; Прелова, И.Н.; Колезнев, А.С. (Биополимеры и клетка, 1986)
Описана установка для аналитического электрофореза в свободном потоке в комплексе с оптическим сканатором и мини-ЭВМ. Приведены результаты измерений подвижности клеток Е. coli эритроцитов барана, гемоглобина лошади, бычьего сывороточного альбумина. Описано установку для аналітичного електрофорезу у вільному потоці в комплексі з оптичним сканатором і міні-ЕОМ. Наведено результати вимірювань рухливості клітин Е. coli еритроцитів барана, гемоглобіну коня, бичачого сироваткового альбуміну. A free-flow electrophoresis device combined with optical scanner and microcomputer is described. In the device the sample is continuously pumped into the vertical stream of buffer. When constant electric field is applied at the right angle with the stream, the sample band is separated into fractions. The magnitudes of fraction displacement are measured by the scanner, and the computer provides the calculation of electrophoretic mobility of fractions. Runs last only for 10 minutes. The technique is illustrated by E. coli, sheep erythrocytes, bovine serum albumin, horse hemoglobin. It may be applied to determine isoelectric points of proteins for rapid measurement of electrophoretic mobility of cells in fermentation.